Acute or Short-term Effects of Whey Protein Alone or Along with Carbohydrate on Inflammation: A Systematic Review of Clinical Trials: Acute Effects of Whey on Inflammation - Akbari, Ali; Moazen, Mahsa; Babajafari, Siavash; Abdollahzadeh, Seyedeh Maryam; Ranjbar Zahedani, Maryam; Sasani, Najmeh; Kazemi, Asma (Galen Medical Journal, 2023)
Background: Excessive inflammatory response is associated with several diseases. Re-cently, there has been an increasing trend for investigation of the acute or short-term effects of whey protein alone or in combination with carbohydrates on inflammato-ry status, especially in athletes. This systematic review aimed to clarify these effects. Materials and Methods: PubMed, Scopus, and Web of Science databases were searched from January 1990 to September 2021, without language restriction. Adult studies examining the effects of whey protein alone or together with carbohydrates on interleukin-6, tumor necrosis factor-α, and C-reactive protein levels with a maximum duration of 15 days and with at least one comparison group were included. The quality of studies was determined using the Cochrane risk of bias tool. Results: Twenty-five studies met the inclusion criteria. Significant reductions in inflammatory markers was observed in seven out of 25 studies (28%). However, one out of 25 studies (4%) re-ported a significant increase in inflammatory status. Among those studies comparing the effects of whey protein alone with non-protein or protein-containing groups, 18.18% (two out of 11) and 10% (one out of ten) of the trials revealed a significant decrease in the markers, respectively. Moreover, of those studies comparing whey protein plus carbohydrate with non-protein or protein-containing groups, 33.33% (two out of six) and 40% (two out of five) of them showed a significant reduction in the inflammatory response, respectively. The quality of the majority of studies (84%) was poor. Conclusion: It seems that whey protein alone or the combination of it with carbohydrates may not affect the inflammatory markers in the short run (PROSPERO registration number: CRD42021273915).